2020
DOI: 10.5194/hess-2019-685
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A robust objective function for calibration of groundwater models in light of deficiencies of model structure and observations

Abstract: Abstract. Groundwater models require parameter optimization based on the minimization of objective functions describing, for example, the residual between observed and simulated groundwater head. At larger scales, constraining these models requires large datasets of groundwater head observations, due to the size of the inverse problem. These observations are typically only available from databases comprised of varying quality data from a variety of sources and will be associated with unknown observational unce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The model structure is based on a comprehensive hydro-stratigraphic model for Denmark and parameterized through calibration against objective functions based on 305 discharge stations and 25,981 hydraulic head observation wells for the period 2000-2010 (for the current application run for the period 2002-2014). The main objective functions are Kling-Gupta efficiency (KGE) [70] and percent bias (Pbias) for streamflow, and continuous ranked probability score (CRPS) values for groundwater heads [53]. Details on the model data, construction, calibration, and validation can be found in [71], while calibration statistics will be presented in brevity in the Result section.…”
Section: Catchment Wb Et Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The model structure is based on a comprehensive hydro-stratigraphic model for Denmark and parameterized through calibration against objective functions based on 305 discharge stations and 25,981 hydraulic head observation wells for the period 2000-2010 (for the current application run for the period 2002-2014). The main objective functions are Kling-Gupta efficiency (KGE) [70] and percent bias (Pbias) for streamflow, and continuous ranked probability score (CRPS) values for groundwater heads [53]. Details on the model data, construction, calibration, and validation can be found in [71], while calibration statistics will be presented in brevity in the Result section.…”
Section: Catchment Wb Et Estimatesmentioning
confidence: 99%
“…In the literature, ET datasets from the remote-sensing and surface water balance approaches have been compared and studied (e.g., [7,8,53,54]). For example, [17,20] compared water balance ET estimates to ET estimates based on hydrological modeling and RS methods over central Europe and Canada, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, F obs (x) is represented by a Heaviside step function, H(x − y); that is, the observation is assumed to be known perfectly. Recent work, however, has demonstrated that model fitting through CRPS minimization is more robust when observational uncertainty is represented explicitly (Schneider et al, 2020). Given this, and the significant uncertainty in daily passive microwave SIC estimates (e.g., Ivanova et al, 2015), we assess the benefits of including the observational uncertainty provided with OSI-SAF SIC in the representation of F obs (x).…”
Section: Coefficient Estimation and Observational Uncertaintymentioning
confidence: 99%
“…The mean errors per model grid then were weighted based on the number of observations-with a weight of 1 for cells with one observation, a weight of 2 for cells with two to nine observations, a weight of 3 for cells with ten to 99 observations, and a weight of 5 for cells with 100 or more observations. The final objective function for groundwater heads was formulated using the Continuous Ranked Probability Score (CRPS), as described by [61]. The CRPS-based approach was chosen because conventionally used squared-errorbased objective functions are particularly sensitive to large residuals.…”
Section: Hydrological Model-calibration Setupmentioning
confidence: 99%